2019
DOI: 10.2147/dddt.s208328
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ginsenoside Rg3 protects mouse leydig cells against triptolide by downregulation of miR-26a</p>

Abstract: Background Ginsenoside Rg3 has been reported to exert protection function on germ cells. However, the mechanisms by which Rg3 regulates apoptosis in mouse Leydig cells remain unclear. In addition, triptolide (TP) has been reported to induce infertility in male rats. Thus, this study aimed to investigate the protective effect of Rg3 against TP-induced toxicity in MLTC-1 cells. Methods CCK-8, immunofluorescence assay, Western blotting and flow cytometry were used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that Leydig cells play an important role in testosterone production and spermatogenesis ( Zirkin and Papadopoulos, 2018 ), and triptolide was shown to inhibit superoxide dismutase expression, which increased intracellular ROS in rat Leydig cells, finally inducing oxidative stress damage and cell death ( Hu et al, 2015 ). In addition, triptolide increased miR-26a expression in rat Leydig cells, which decreased GSk 3β mRNA levels and inhibited testosterone production ( Liang et al, 2019 ). Another study also reported that triptolide induced Leydig cell apoptosis, and this effect might be highly associated with miR-200 ( Miao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Leydig cells play an important role in testosterone production and spermatogenesis ( Zirkin and Papadopoulos, 2018 ), and triptolide was shown to inhibit superoxide dismutase expression, which increased intracellular ROS in rat Leydig cells, finally inducing oxidative stress damage and cell death ( Hu et al, 2015 ). In addition, triptolide increased miR-26a expression in rat Leydig cells, which decreased GSk 3β mRNA levels and inhibited testosterone production ( Liang et al, 2019 ). Another study also reported that triptolide induced Leydig cell apoptosis, and this effect might be highly associated with miR-200 ( Miao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, triptolide exerts renal protective, cardioprotective and antiangiogenesis functions by regulating the expression of miRNAs (38)(39)(40)(41)(42). Furthermore, miRNAs are closely associated with the multiorgan toxicity of triptolide (23,43). Tables Ⅰ and Ⅱ list evidence supporting miRNAs as pivotal mediators in the pharmacological properties of triptolide.…”
Section: Triptolide Modulates the Expression Of Mirnasmentioning
confidence: 99%
“…Thus, investigating the molecular mechanisms underlying their activities is highly warranted. As a biologically active ingredient derived from the Chinese herb, Tripterygium wilfordii Hook F., recent studies have demonstrated that triptolide exerts effects on the expression of a series of endogenous miRNAs, which in turn employ several downstream cellular factors to achieve its multiple pharmacological activities, highlighting miRNAs as critical mediators for triptolide-induced effects (18,20,21,23,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). However, determining the exact role of these miRNAs is limited by the in vitro models offered by these studies.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The dose of TP was calculated based on previous studies. 16,17 Flow Cytometric Analysis Apoptosis in MLTC-1 and in TM3 cells was detected by an Annexin V-FITC/PI Apoptosis Detection Kit (Sigma-Aldrich, St. Louis, MO, USA). Cells were washed three times with pre-cold PBS, and then were resuspended in 500 μL of binding buffer.…”
Section: Cell Counting Kit-8 (Cck-8)mentioning
confidence: 99%